PELATIHAN PROGRAM SIARAN RADIO SEBAGAI MEDIA ALTERNATIF DI LINGKUNGAN SANTRI - Syaifudin, Ahmad Anif; Muizzah, Awendsa Urfatunnisa Tasyaul (Artinara, 2025)
Radio is an important mass media for the public seeking information, entertainment, and education, and Uniss FM Radio with the tagline "Radionya Sobat Kendal" which is managed by students of the Communication Studies Program at UNISS Kendal. Since COVID-19 appeared in March 2020, many changes in the way of life have occurred in society; from how to interact, buy and sell, and maintain health to how to study. From this background, the Community Service Team (PKM) led by Lecturers of Communication Science FISIP UNISS and Uniss FM Radio seeks to take a strategic role that focuses on health and education counseling in the Islamic students' environment. The purpose of this program activity is to provide counseling on the importance of radio broadcast programs as an alternative media in an effort to fight the COVID-19 pandemic in the Islamic students' environment using role-playing and FGD methods. The result of this activity is that students have an awareness of the importance of radio broadcast programs as a medium that provides access to learning and healthy lifestyle information services during a pandemic. In addition, the students understand radio broadcast production management by role-playing as professional radio broadcasters.